Role and Commitment Cadre in Preventing PD3I and Implementation MVMH for The Immunization Completeness Status in The Health Boyolangu, Tulungagung Regency - Sujjadah (Journal of Global Research in Public Health, 2021)
Infant health is very important for the basis of perfect growth and development in order to get a quality generation. One of the programs to maintain the health of babies to avoid very dangerous diseases is immunization. Cadres are the spearhead of services at the Integrated Healthcare Center and play an important role in convincing the community to provide complete immunizations for their children. The completeness of basic immunization is not only influenced by the level of knowledge of the mother as a predisposing factor, but also influenced by the role and commitment of cadres and then equipped with MVMH media. The purpose of this study was to determine the effect of the dependent variable and the independent variable simultaneously or partially. By taking the research subject, Mrs. Toddlers with an age range of 1 to 5 years who are registered at the Integrated Healthcare Center and have KMS. This study uses a descriptive quantitative correlation approach, and uses multiple regression analysis, t test, F test, and uses the SPSS for windows application version 16.0. The results of the multiple regression analysis showed that there was an influence between the variables of the role of cadres and the commitment of cadres in preventing diseases that could be prevented by immunization (PD3I) and the implementation of My Village My Home (MVMH) on the status of completeness of immunization in the working area of ​​the Boyolangu Public Health Center which had an effective contribution. of 79.5% of the completeness of immunization status